Severe Burnout and Poor Mental Health Among Healthcare Workers 6 Months After COVID-19 Pandemic Declaration: What Can We Learn for Future Emergencies?. (November 2021) - Kim, Son Chae; Sloan, Christine; Chechel, Laura; Redila, Matt; Ferguson, Jennifer
Abstract : OBJECTIVES: The aim of this study was to examine the predictors associated with severe burnout and poor mental health among healthcare workers during the COVID-19 pandemic as a learning opportunity for future emergent situations. BACKGROUND: Modifiable predictors of mental health need to be further examined and quantified to prioritize human resource support in organizations as healthcare workers confront stressful situations. METHODS: A cross-sectional survey was conducted among 271 healthcare workers from September 8 to October 10, 2020. RESULTS: Approximately one-third reported severe burnout, as well as moderate/severe anxiety and depression. Feeling protected working with COVID-19 patients, high family functioning, and spirituality were associated with 2- to 4-fold lower odds of severe burnout. Satisfaction with the organization's communications predicted 2-fold lower odds of anxiety, whereas high resilience was associated with almost 4-fold lower odds of stress and depression. CONCLUSIONS: Healthcare organizations may consider adopting programs to foster resilience, family and spiritual support, and effective communication strategies to reduce burnout and poor mental health among healthcare workers during pandemics and other situations of high stress.